2023
DOI: 10.3389/fmicb.2023.1216534
|View full text |Cite
|
Sign up to set email alerts
|

Influence of probiotic supplementation on the growth performance, plasma variables, and ruminal bacterial community of growth-retarded lamb

Abstract: IntroductionGrowth-retarded lambs would reduce the economic incomes of sheep farming. Nutritional interventions are supposed to promote gastrointestinal health and the compensatory growth of growth-retarded lambs. This study evaluated the effects of probiotic supplementation on the growth performance, plasma characteristics and ruminal bacterial community of growth-retarded lambs.MethodsTwenty-four 50-days old male Hu lambs, including 8 healthy lambs (13.2 ± 1.17 kg) and 16 growth-retarded lambs (9.46 ± 0.81 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…V-type proton ATPase is a multi-subunit protein that transfers protons depending on energy produced by ATP hydrolysis, which plays an important role in nutrient absorption and balancing of the intracellular and extracellular environments. A previous study showed that growth-retarded lambs had lower VFA concentrations in the rumen when fed the same diets [13], indicating that lower protein expressions of nutrient transporters in the ruminal epithelium were also the cause of the lower VFA production of GRY.…”
Section: Proteome Analysismentioning
confidence: 96%
“…V-type proton ATPase is a multi-subunit protein that transfers protons depending on energy produced by ATP hydrolysis, which plays an important role in nutrient absorption and balancing of the intracellular and extracellular environments. A previous study showed that growth-retarded lambs had lower VFA concentrations in the rumen when fed the same diets [13], indicating that lower protein expressions of nutrient transporters in the ruminal epithelium were also the cause of the lower VFA production of GRY.…”
Section: Proteome Analysismentioning
confidence: 96%
“…Henderson et al measured rumen microbial samples from 35 countries and 32 animal species to assess whether they were influenced by diet, host, or geographic location and found that differences in microbial community composition were primarily attributable to diet, with a lesser influence of the host (Henderson et al, 2015 ). In addition, in long-term feeding trials, it was found that adding enzyme preparations, plant extracts, probiotics, herbal additives, and other substances to animal feed can improve the gastrointestinal health of livestock and poultry; enhance the body's immune system; promote the digestion and absorption of nutrients, which will have a positive impact on the growth of livestock and poultry; and reduce the cost of feeding to a certain extent (Mao et al, 2023 ; Wang et al, 2023a ).…”
Section: Introductionmentioning
confidence: 99%